Analisis Pemilihan Kepala Desa Serentak terhadap Demokrasi Lokal di Desa Tanjung Kabupaten Aceh Tamiang - Ramadani Ramadani; Irwan Nasution; Usman Tarigan (PERSPEKTIF, 2018)
The election of the Village Head shall be directly elected by the villagers of the Republic of Indonesia who meet the requirements with a term of office of 6 years from the date of inauguration. The community of Tanjung village with a population of nearly 2000 more of its inhabitants, Yang has various racial tribes respectively. In the election of the village head there should be support and participation of the Tanjung village community to determine who is eligible to serve as the village head. Why is it made so that the public is free and entitled to choose the desired leader. The election of the village head is supported by the villagers of Tanjung and for his cooperation with the organizing committee of the village head election. To become a candidate the village head must meet the conditions that have been set so that the performance of the village head can be more leverage and better know the rules.